Sistem Informasi Sepeda Motor Dengan Metode User Centered Design - Gusto Gibeon Ginting; I Gusti Ngurah Anom Cahyadi Putra; Made Agung Raharja; Ngurah Agus Sanjaya ER; I Ketut Gede Suhartana; Gst. Ayu Vida Mastrika Giri (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Today, vehicles are a major need for humans, especially motorcycles. In Indonesia alone the numberof motorcycle population is more than other types of vehicles. The use of motorbikes is consideredmore effective because of low operational costs, economical fuel consumption and moreenvironmentally friendly, and a wider range of mobility due to their not too large size and easy use.Because of this, various brands of industrial companies are circulating in the market, so that it is difficultfor people to choose a motorbike. To realize this, a research entitled Motorcycle Information SystemUsing the User Centered Design Method was carried out. In this study, the researcher will later add arecommendation feature to the built website, this feature will later compare in terms of a smaller valuethan the variable inputted by the user, to run this feature, the researcher adds a selection sort algorithmas an algorithm for comparing values between variables.This study aims to design a website-based user interface and user experience. Where it is, proportionalto the increase in the number of purchases of existing motorcycles. The website that has been madewas tested on the General Public and Informatics Students with a total of 20 respondents. To find outthe level of satisfaction of respondents in using the motorcycle recommendation website, usabilitytesting was carried out using the system usability scale method. This method measures the usability ofa computer system according to the user's subjective point of view by filling out a Likert-scalequestionnaire. The website that has been made is tested on the General Public and InformaticsStudents. To find out the level of satisfaction of respondents in using the motorcycle recommendationwebsite, usability testing was carried out using the system usability scale method. This methodmeasures the usability of a computer system according to the user's subjective point of view by fillingout a Likert-scale questionnaire.